The positive and negative effects of WeChat on parent-child relationship maintenance - Wu, Yiwen; YIN, Yiqiu (Advances in Social Sciences Research Journal, 2021)
WeChat has been deeply involved in every aspect of Chinese people’s life, and has exerted great influence on the Chinese family and parent-child relationship.This paper discusses the effects of WeChat on Chinese family stability, consumption pattern, family function, parent-child relationship and other aspects through interviews and literature review.The results show that WeChat has both positive and negative effects on the Chinese family and parent-child relationship.The negative effect of WeChat should arouse the great attention of technical developers and sociologists so that a good balance between the application and restriction of WeChat can be achieved.